2015
DOI: 10.1177/0091415015603608
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Teacher Association, Soup Kitchen, Church, or the Local Civic Club? Life Stage Indicators of Volunteer Domain

Abstract: Gaps in existing literature hinder our knowledge of how life stage-related identities (e.g., worker, parent, student, etc.) influence individuals' decisions about whether and how to get involved in community service. Interventions to increase volunteerism throughout the life course require a more nuanced understanding of this relationship. We use multinomial logistic models to analyze how life phase factors relate to involvement in different types of voluntary organizations across the adult life course in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
(64 reference statements)
2
3
0
Order By: Relevance
“…This result is supported by other studies indicating that participation in faith-based communities appears to increase the flow of health information that may increase disease screening and promote health maintenance behaviors (Koenig, 2012;Salmoirago-Blotcher et al, 2011). This is in line with several studies suggesting that religious participation can be regarded as a type of volunteering and active social engagement for this generation of older adults (Carr et al, 2015;Marcum, 2013;Shandra, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result is supported by other studies indicating that participation in faith-based communities appears to increase the flow of health information that may increase disease screening and promote health maintenance behaviors (Koenig, 2012;Salmoirago-Blotcher et al, 2011). This is in line with several studies suggesting that religious participation can be regarded as a type of volunteering and active social engagement for this generation of older adults (Carr et al, 2015;Marcum, 2013;Shandra, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Activities to promote successful aging often include employment, leisure, religious participation, membership in community associations, volunteerism, education, and political activism (Rowe & Kahn, 2015). Such activities are influenced not only by individuals' choices, but also by their opportunities in interpersonal, communal, environmental, and cultural contexts (Carr et al, 2015). Involvement in highly valued social roles appears to be strongly linked to psychological well-being, especially when the older individual does not receive adequate emotional support (Matz-Costa et al, 2012).…”
Section: Successful Aging Activities and Perceived Healthmentioning
confidence: 99%
“…Social class determines what role parents think they should play in their children's life, whether they should be strongly and broadly involved to foster their abilities or let them develop their capacities on their own while taking care only of their emotional and existential needs. This idea seems also in line with studies on social inequality in volunteerism and PTA-membership showing that some parents perceive or justify school involvement as moral duty towards their child, and an act of civic engagement (Barthélémy 1995;Héran 1988;Carr et al 2015;Fisher 2018).…”
Section: Cultural Capital Educational Resources and Cultural Logicssupporting
confidence: 79%
“…Psychologists have primarily used motivational theories to explain why people decide to help, and specifically why they decide to take up volunteering ( Wilson, 2012 ). In answering whether motives can explain helping behavior, previous studies found that the decision to provide help is also influenced by the stage of life in which one finds oneself and the related life roles, such as education, career, family, and retirement (e.g., Carr et al, 2015 ; Yamashita et al, 2019 ). Social-emotional selectivity theory explains these shifts in priorities and decisions as we age ( Carstensen, 1992 ), and helps us understand the motives behind helping behavior.…”
Section: Introductionmentioning
confidence: 99%